Diversity and Percent Covers of Aquatic Plants in Parit Lake Tambang District Kampar Regerency Riau Province - Qurata Ayunin; Efawani Efawani; Isma Mulyani (Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
Parit Lake is one of the Oxbow Lakes located in Parit Baru Village, Tambang District, Riau Parovince. The lake is overgrown with various kinds of aquatic plants that almost cover the surface of the lake. This study aims to determine the diversity and percent covers of aquatic plants carried out in July 2022. The method use in this study is a survey method, where Parit Lake is used as a research area and the method use in observation of aquatic plants is the Belt Transek method. Menwhile, the method use in measuring water quality is direct observation and laboratory scale. Sampling of aquatic plants is carried out 1 times in a period of one month. The aquatic plants obtained were identified based on Van Steenis (1981). The results showed that there are 5 species of aquatic plants divided into 3 classes and 5 families, namely Eichhornia crassipes, Salvinia molesta, Limnocharis flava, Ipomea aquatica, and Cyperus rotundus. The diversity index of aquatic plants species in Parit Lake is relatively low with a value of 0,7. The percent covers of aquatic plants is relatively tight with a value of 60% with the highest covers of the Salvinia molesta species at 25%, while the lowest in the species Limnocaris flava is 3,75%.